Adaptationand Development in Thai Community Enterprises during the COVID-19 Crisis - Dr. Usa Sutthisakorn, Samchai Jirapatarasil, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One of the sectors in Thailand most impacted by the COVID-19 pandemic is the entrepreneurial sector, especially community enterprises,that need to constantly adapt and develop for survival. This article presents case studies of adaptation and self-improvement in six community enterprises during the COVID-19 pandemic. An Adaptation and Development Model of Community Enterprise throughout Covid-19 is proposed, which consists of 1)online marketing 2) the creation of new products to meet the needs of new customers 3) the expansion of marketing channels, and 4) knowledge development. The new concept of 4Cs marketing, focusing on the consumers‟ perspective, is proposed as community enterprisestrategies. Additionally, innovation and knowledge management, are also important in the knowledge development of community enterprises.